2001
DOI: 10.1152/ajpregu.2001.281.6.r1877
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of an agouti signaling protein variant and characteristics of its cognate radioligand

Abstract: Agouti signaling protein (ASIP), the human (h) homolog of agouti, is an endogenous melanocortin peptide antagonist. To date, characterization of this protein has been performed with recombinant protein only and without the availability of an ASIP/agouti radioligand. In this report we describe the functional characteristics of a chemically synthesized truncated ASIP variant, ASIP-[90-132 (L89Y)], and the binding characteristics of its cognate radioligand, (125)I-ASIP-[90-132 (L89Y)]. Similar to full-length reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…We have previously shown that the chemically synthesized C-terminal region of AGRP com- petitively antagonizes ␣-MSH at melanocortin receptors with potency equal to that of the full-length proteins (Yang et al, 1999a). This is consistent with similar findings for agouti (Yang et al, 2001). In this study, we examine the molecular basis of ligand-receptor interaction between AGRP and hMC4R by pharmacologically studying AGRP fragments and analyzing the function of melanocortin chimeric receptors.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that the chemically synthesized C-terminal region of AGRP com- petitively antagonizes ␣-MSH at melanocortin receptors with potency equal to that of the full-length proteins (Yang et al, 1999a). This is consistent with similar findings for agouti (Yang et al, 2001). In this study, we examine the molecular basis of ligand-receptor interaction between AGRP and hMC4R by pharmacologically studying AGRP fragments and analyzing the function of melanocortin chimeric receptors.…”
Section: Discussionsupporting
confidence: 82%
“…This cell line has previously been characterized [36, 37]. Cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) with 10% fetal bovine serum (FBS) with 100 U/ml penicillin and 100 U/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 2 The Structures of ASIP exhibits a slope of near unity, demonstrating competitive antagonism, and K i values, determined from the intercept, lie within the range previously established for both full-length and C-terminal ASIP ( Table 2). [17][18][19] NMR structure of ASIP-YY Structure determination was performed using the same strategy previously applied to AgRP(87-132). 11 Specifically, a standard suite of homonuclear Table 2 and insets.)…”
Section: Design Synthesis and Pharmacology Of A Functional Asip C-tementioning
confidence: 99%